Assessment of the level of knowledge about infodemic in two university institutions in Peru - Takahashi-Ferrer, Carolina Mayo (2024)
Objective: The general purpose of this research study is to describe the understanding of students belonging to two universities; about the phenomenon of the infodemic, which arose during the period of the COVID-19 pandemic (Lima-2023). Method: The study is observational, with a non-experimental design, cross-sectional and with a descriptive level, where thepopulation was selected from two universities located in the metropolitan area of the city of Lima, between a public institution and another private one, with a sample of 100 students from the last years of their university studies. Regarding the sample, data were evaluated and collected using a research instrument, with the survey being the selected modality, which was developed independently. Result: The results acquired from graphs 21 to 29 show that, although there are 22% of students who did know about the concept of infodemic and who had also received an explanation at the university on the subject, 88% of the students had no idea about this infodemic phenomenon that appears during the pandemic period and they did not receive information about the topic either. Conclusion: It was discovered that the majority of students from both institutions do not have knowledge or are not informed regarding the phenomenon of the infodemic.